LITERATURE REVIEW: DERMATOLOGICAL MANIFESTATIONS IN PATIENTS INFECTED BY COVID-19 - Araujo Hottz Klein, Amanda; Proença Benacchio, Katriel (Health and Society, 2023)
Objective: Advances in understanding the pathophysiology of Covid-19 identify the need to adapt the management, in order to correspond to its specificity. In this way, the largest organ in the human body becomes the target of manifestations in a significant part of those infected by Sars-Cov-2. Method: A literature review was carried out on PubMed platforms with the descriptors “Covid 19”, “Manifestations”, and “Skin” and Lilacs with the descriptors “Covid 19” and “skin”. From the results obtained, articles that elucidated dermatological manifestations were selected. Results and Discussion: The skin lesions most frequently related to Covid-19 were rash, erythema, exanthema, papules, vesicles, petechiae and hives. Conclusion: It is still not possible to state that skin lesions, in isolation, are an indicator of disease severity, however, lesions with vascular involvement tend to have a worse prognosis, deserving differentiated systemic attention, due to their greater potential for severity.